X-ray powder diffraction reference patterns for Bi1−xPbxOCuSe. Issue 3 (September 2016) - Wong-Ng, W.; Yan, Y.; Kaduk, J.A.; Tang, X.F.
Abstract : The structures and powder X-ray reference diffraction patterns of the "natural superlattice" series Bi1− x Pb x OCuSe ( x = 0, 0.02, 0.04, 0.06, 0.08, and 0.10) have been investigated. As the ionic radius of Pb 2+ is greater than that of Bi 3+, the unit-cell volume of Bi1− x Pb x OCuSe increases progressively from x = 0 to 0.1, namely, from 137.868(5) to 139.172(11) Å 3, as expected. The structure of Bi1− x Pb x OCuSe is built from [Bi2(1− x ) Pb2 x O2 ] 2(1− x )+ layers normal to the c -axis alternating with [Cu2 Se2 ] 2(1− x )− fluorite-like layers. Pb substitution in the Bi site of Bi1− x Pb x OCuSe leads to the weakening of the "bonding" between the [Bi2(1− x ) Pb2 x O2 ] 2(1− x )+ and the [Cu2 Se2 ] 2(1− x )− layers. Powder patterns of Bi1− x Pb x OCuSe were submitted to be included in the Powder Diffraction File.